Pengembangan LKM Berorientasi KKNI untuk Penguatan Scientific Approach pada Mata Kuliah Persamaan Diferensial - Wasilatul Murtafiah; Edy Suprapto (LPPM Press, 2014)
This research aims to develop LKM (Student Worksheet) with KKNI oriented (IndonesianNational Qualifications Framework) for strengthening the scientific approach to thecourse Differential Equations. Knowing how the level of validity, practicality andeffectiveness of LKM (Student Worksheet) with KKNI oriented (Indonesian NationalQualifications Framework) for Strengthening Scientific Approach to DifferentialEquations courses have been developed. In accordance with the problems studied, themethod used in this research is descriptive method with quantitative approach developedreferring to the phase of Fenrich P, (2007). Data collection techniques used wereobservation, testing, and deployment of the type of closed questionnaire. Data analysistechnique was done by descriptive analysis of quantitative and qualitative (mixingmethod).This research activity has been carried out through several phases, such asanalysis, planning, design, development, and implementation. The result showed that LKM(Student Worksheet) with KKNI oriented (Indonesian National Qualifications Framework)for strengthening the scientific approach Differential Equations courses fulfilled thecriteria of validity and practicality. Developed Student Worksheet can not be said to be agood device because it has not fulfilled the criteria of effectiveness.